The proposed quality improvement of tofu production at UD. XYZ using DMAIC method - Purbantari, Adek Dhea Resmi; Zunaidi, Rizqa Amelia (Universitas Mercu Buana, 2024)
Tofu is known as people's food because the price is cheap and easily accessible by all levels of society. Tofu is in great demand. Besides its affordable price, this food is also healthy and can be processed into various dishes. Quality control is essential for a company to minimize the costs caused by product defects. It can help the company if there are irregularities in the production process. With a large number of irregularities in production, the company will experience losses in quality, cost and quantity. This research was conducted to control and improve the quality of tofu at UD. XYZ uses the Six Sigma method through the Define, Measure, Analyze, Improve, and Control stages. Based on the analysis results, the sigma value is 3.4, and the DPMO value is 29,189, indicating that improvement is still needed to reduce defects that arise so that the sigma value can be increased. Based on this research, it is suggested to improve the sigma quality by investing time and money to train new company employees and improve the equipment used in the tofu production process. It is purchasing automated equipment to support better production processes. Research on enhancing the quality of tofu production should be carried out periodically at UD. XYZ, as part of the company's continuous improvement.